(3aJM GdLdjd TQM eNJUQ Ndjds - (3eMeO Hf EHQGgje GdJJGFi CHh YHO Gddg TeS GdOjfs; (3Ndjd Hf ESMGb Hf ehSi, VjGA GdOjf GdoLrfpOj GdeGdcj GdeUQj,J (B776 (3g` s
(3ChdgG (B:s
(3HGH GdRcGI gPG GdHGH jSei cJGH GdRcGI hcJGH GdPHGFM , hGdPcGI ai GddZI CUdgG GdJeGe , aeYfi PcjJ GdPHjMI (B: (3CJeeJ PHMgG , hPcjJ GdfGQ CJeeJ EjbGOgG s
(3BNQgG (B:s
(3hGdMVGfI eYfGgG Cf GdMGVfI EPG CjSQJ Ohf GdCH de Jcf Ydi GdCH Scfi Ydi gPG Gdbhd hHg jHWd bhd R hCeG GdScfi ajeG jNU GdeMVhf aYdi GdCH CJaGbkG GfJgi s
(3fSNI LjOI eUMMIs
(3HYV YHGQGJgG HGdMeQIs
(3hMhGagG eJBcdIs
(3hHgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdeGdcjs